Diseño de Herramienta SIG Para La Gestión de La Información de Diagnósticos Técnicos en La Subdirección de Análisis de Riesgos y Efectos del Cambio Climático del Instituto Distrital de Gestión de Riesgos y Cambio Climático (IDIGER) de La Ciudad de Bogotá (2021)
The implementation of Geographic Information Systems (GIS) in risk management improves the way in which the data necessary for decision-making is acquired, for this work we rely on the Technical Assistance group of the District Institute of Risk Management and Change Climático (IDIGER) of the city of Bogotá, a form was designed through the application of SURVEY 123 of ESRI so that professionals who attend emergencies can take the data directly in the field obtaining information in an easy, fast and reliable way. to later apply a model based on ARCGIS software tools that will take said data to a Geodatabase (GDB) where the information will be organized, unified and standardized. With the design it was discovered that the way in which the data is currently handled in the group is not ideal since it does not unify the information, it presents fields that are not necessary or are empty, hence the importance of improving processes supported by tools S.I.G. Being a work that was carried out thinking about the need for an entity that provides a vital service for the city of Bogotá, if it is implemented it will facilitate decisionmaking, help in the work of the entity, preserve the life of citizens and avoid economic losses.